Factors that influence the Quality Dimensions of National Health Insurance Participant Satisfaction with Outpatient Services at the Community Health Center - Nurbaiziah, Nurbaiziah; Efendy, Ismail; Fitriani, Arifah Devi (Jurnal Perilaku Kesehatan Terpadu, 2023)
Introduction The Teunom Community Health Center experienced a significant decrease in JKN participants at the Teunom Community Health Center by 13,099 people, in 2021 there were 12,904 people, while the number in 2022 was 12,871 people.The research method is a cross sectional study approach. accidental sampling sample. Univariate, bivariate and multivariate quantitative data through logistic regression tests.The results of the research, univariate and bivariate tests of technical competence do not affect patient satisfaction, p-value= 0.140, access to services does not affect patient satisfaction, the value is p-value= 0.647, human relationships affect patient satisfaction p-value= 0.001, comfort affects patient satisfaction p-value= 0.0001, information does not influence patient satisfaction p-value= 0.731 and timeliness influences patient satisfaction p-value= 0.037. Based on multivariate relationships between people OR= 9.459, comfort OR= 10.903 and timeliness OR= 2.875 and the most dominant factor influencing patient satisfaction is the comfort variable with a value of OR = 6.600. In conclusion, the variables of human relations, comfort and timeliness, influence patient satisfaction. The variables technical competence, access to services and information do not influence outpatient satisfaction at the Teunom Community Health Center, Teunom District. factors influence patient satisfaction, human relations, comfort and timeliness. The dominant factor in patient satisfaction is the comfort variable.It is recommended that the Health Service analyze and evaluate the quality of services at the Puskesmas. For Puskesmas to improve the performance of motivation for employees to be friendlier in responding to and responding to patient complaints.